Exposure to Bisphenol A Analogs and the Thyroid Function and Volume in Women of Reproductive Age—Cross-Sectional Study - Milczarek-Banach, Justyna; Rachoń, Dominik; Bednarczuk, Tomasz; Myśliwiec-Czajka, Katarzyna; Wasik, Andrzej; Miśkiewicz, Piotr (Frontiers in Endocrinology, 2021)
Bisphenols (BPs) are commonly known plastifiers that are widely used in industry. The knowledge about the impact of BPs on thyroid function is scarce. Proper thyroid functioning is especially important for women of reproductive age, as hypothyroidism affects fertility, pregnancy outcomes and the offspring. There are no studies analyzing the influence of BPs on thyroid function and volume in non-pregnant young women. The aim of this cross-sectional study was to evaluate the relationship between bisphenol A and its 10 analogues (BPS, BPC, BPE, BPF, BPG, BPM, BPP, BPZ, BPFL, BPBP) on thyroid function and volume in women of reproductive age. Inclusion criteria were: female sex, age 18-40 years. Exclusion criteria were: history of any thyroid disease, pharmacotherapy influencing thyroid function, pregnancy or puerperium, diagnosis of autoimmune thyroid disease during this study. Venous blood was drawn for measurement of thyrotropin (TSH), free thyroxine, thyroid peroxidase antibodies, thyroglobulin antibodies, BPs. Urine samples were analyzed for: ioduria and BPs. Ultrasound examination of thyroid gland was performed. 180 participants were included into the study. A negative correlation was found between urine BPC and the thyroid volume (R= - 0.258; p=0.0005). Patients with detected urine BPC presented smaller thyroid glands than those with not-detected urine BPC (p=0.0008). A positive correlation was found between TSH and urine BPC (R=0.228; p=0.002). Patients with detected urine BPC presented higher concentrations of TSH versus those with not-detected urine BPC (p=0.003). There were no relationships between any of serum BPs as well as the other urine BPs and thyroid function and its volume. The only bisphenol that demonstrated the relationship between thyroid function and its volume was BPC, probably because of its chemical structure that most resembles thyroxine. Exposure to this BP may result in the development of hypothyroidism that could have a negative impact on pregnancy and the offspring.